2008
DOI: 10.1002/art.23912
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Childhood Health Assessment Questionnaire in active juvenile systemic lupus erythematosus

Abstract: The C-HAQ showed moderate responsiveness to clinical change, construct validity, good feasibility, internal consistency, and discriminative ability. These findings demonstrate that the C-HAQ represents a good measure to capture disability in patients with active juvenile SLE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 20 publications
0
23
0
Order By: Relevance
“…Pain score was assessed at the time of study visit by participant self-report on a Likert scale of 0 to 10, with higher scores indicating higher pain levels. Physical functioning of SLE and MCTD subjects was also assessed by survey of the parents/legal guardians using the Child Health Assessment Questionnaire (CHAQ), a validated 30-item instrument that measures 8 functional ability domains and calculates a disability index ranging from 0 to 3 (higher index indicates more disability) [37, 38]. …”
Section: Methodsmentioning
confidence: 99%
“…Pain score was assessed at the time of study visit by participant self-report on a Likert scale of 0 to 10, with higher scores indicating higher pain levels. Physical functioning of SLE and MCTD subjects was also assessed by survey of the parents/legal guardians using the Child Health Assessment Questionnaire (CHAQ), a validated 30-item instrument that measures 8 functional ability domains and calculates a disability index ranging from 0 to 3 (higher index indicates more disability) [37, 38]. …”
Section: Methodsmentioning
confidence: 99%
“…Responsiveness to change was assessed using standardized response mean (SRM), which has been used in other studies to measure behavioral change (Meiorin et al, 2008; van der Zee, Kap, Rambaran Mishre, Schouten, & Post, 2011). SRM was calculated as the absolute mean change in PA divided by the standard deviation of individuals’ change in score (Cohen, 1977; Meiorin, et al, 2008), as shown in equation (1): italicSRM=italicHigh0.16667emitalicintensity-italicLow0.16667emitalicintensitySD0.16667emofitalicHigh0.16667emitalicintensity-italicLow0.16667emitalicintensity…”
Section: Methodsmentioning
confidence: 99%
“…The Childhood Health Assessment Questionnaire (CHAQ) was incorporated in the transition pathway. The CHAQ measures functional status and is validated for different juvenile rheumatic conditions (Tennant et al 2001, Meiorin et al 2008.…”
Section: Developing the Clinical Transition Pathwaymentioning
confidence: 99%